On Equilibrium Pricing under Parameter Uncertainty - Coles, Jeffrey L.; Loewenstein, Uri; Suay, Jose (Journal of Financial and Quantitative Analysis, 1995)
Prior theoretical work on estimation risk generally has been restricted to single-period, returns-based models in which the investor must estimate the vector of expected returns but the covariance matrix is known. This paper extends the literature on parameter uncertainty in several ways. First, we analyze asymmetric parameter uncertainty in a model based on payoffs. Second, we explore the effects of both symmetric and asymmetric estimation risk on equilibrium asset prices when the covariance matrix for payoffs must also be estimated. Finally, we investigate the effects on equilibrium of asymmetric parameter uncertainty in a simple multiperiod model.